A Review on Metabolic Syndrome and Nutrition - Mesçi, Banu; Erbakan, Ayse; Çaklili, Özge Telci (Journal of Nutritional Therapeutics, 2015)
Metabolic syndrome can be defined as a disorder with occurrence of at least three out of five medical conditions including hyperglycemia, hypertriglyceridemia, high blood pressure, central obesity and low HDL cholesterol levels. In this review we will discuss how to improve poor eating habits which further escalates the risk of cardiovascular disease and diabetes. To treat and moreover to prevent metabolic syndrome, we should make healthy life style changes as our priority goal. Macro and micronutrient composition and metabolically favorable food components have a profound influence on health outcomes. Though Mediterranean and DASH diets are referred as the healthiest diets, there are numerous diets that are as well successful. Positive effects of low carbohydrate diets on glycemic regulation have been shown. Nonetheless, personalized nutrition applications with persistent implementation of these changes are foundations for success. A successful approach also needs regular exercise and behavioral changes.